Pengaruh Metode Story Telling Terhadap Kemampuan Berbicara Peserta Didik Gugus III Jonggat Tahun Pelajaran 2020/2021 - Aspiana Aspiana; Ida Bagus Kade Gunayasa; Muhammad Tahir (Educational Consultant & Counseling Career (EC3) Mataram, 2021)
The problem raised in this research is the influence of the story telling method on the speaking ability of the fourth grade students of Jonggat Group III in the 2020/2021 school year. The aim is to determine the effect of the story telling method on the speaking ability of the Jonggat Cluster III students for the 2020/2021 academic year. The results of this study are expected to be useful theoretically and practically. The concept used in this study is the nature of the story telling method and speaking skills. This type of research is descriptive quantitative research, the data sampling technique is purposive sampling technique (samples aim to take several samples from several populations). Data collection techniques using oral tests. Hypothesis testing was carried out using the T test with the help of SPSS version 23. The results showed the value of the lowest value of the experimental pretest was 20 while the highest was 80 and the lowest value was for the control class 40 and the highest was 85, then for the experimental posttest value, the lowest value was 75 and the highest value was 80. , for the posttest control class the lowest score is 68 and the highest score is 96. This shows that there is an effect of the story telling method on the speaking ability of the fourth grade students of Jonggat Group III in the 2020/2021 school year.